STUDI ALIRAN DALAM CONSTRUCTED WETLAND MENGGUNAKAN TANAMAN CYPERUS PAPYRUS DALAM MENGOLAH LINDI - Bieby Voijant Tangahu (Purifikasi, 2006)
A simple technology to treat leachate is through the use of constructed wetland system using aquatic plant, Cyperus papyrus. The aims of this study were to determine the efficiency of horizontal and vertical flow system in constructed wetland in removing Total N and Total Solid. The dimension of the reactor was 90×30×50 cm with media height of 40 cm. The media was sand with porosity of 47,91 %, time detention of 1 day and flow of 25 l/day. The concentration variations of N are 100 mg/L and 150 mg/L. In horizontal flow reactor with N concentration of 100 mg/L, the highest efficiency of Total N reduction was 90,52 %, and TS reduction efficiency was 62,77 %. In the vertical flow reactor, the highest efficiency of Total N reduction of 91,24 % was achieved when N concentration was 150 mg/L and efficiency for TS reduction was 64,56 % when N concentration was 100 mg/L.